Comparison of Cognitive Function between Intracerebral Haemorrhage Stroke Patients with and without Hypertensive Crisis - Mohammad Arianto Satrio Wicaksono; Cep Juli; Chandra Calista; Uni Gamayani; Aih Cahyani; Paulus Anam Ong (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Intracerebral haemorrhage (ICH) stroke is characterized by neurological dysfunction, caused by focal collection of blood within the brain parenchyma or ventricular system that is not caused by trauma. Hypertension is one of the main risk factors for intracerebral haemorrhage. Hypertensive crisis, which is a more severe type of uncontrolled hypertension may aggravate the cognitive outcomes. The aim of this study was to compare cognitive function between intracerebral haemorrhage stroke patients with and without hypertensive crisis. Methods: This study was a retrospective comparative analytic study, combined with a case-control study from August to November 2020. All medical records of patients with intracerebral haemorrhage, who were admitted to Dr. Hasan Sadikin General Hospital Bandung in 2019, were collected. The total score of mini-mental state examination (MMSE) which was recorded in the medical record was taken and compared between groups using the Mann-Whitney test. The MMSE was conducted on the day of discharge, and the minimum education level of the patients was elementary school.Results: We found a total of 109 medical records with ICH, 67 of which were with hypertensive crisis. The median MMSE score in the hypertensive crisis group was slightly higher than in the non-hypertensive crisis group. Furthermore, there was no statistical difference in MMSE scores between intracerebral haemorrhage patients with and without hypertensive crisis (p-value=0.439). Conclusion: There is no difference in cognitive function between intracerebral haemorrhage patients with and without hypertensive crisis. Further study is of great value to explore the relation between intracerebral haemorrhage patients with and without hypertensive crisis.